Experimental investigation of pore structure and its influencing factors of marine-continental transitional shales in southern Yan’an area, ordos basin, China - Xiao, Hui; Xie, Nan; Lu, Yuanyuan; Cheng, Tianyue; Dang, Wei (Frontiers in Earth Science, 2022)
This work investigates the effects of organic and inorganic compositions on the development of pore structures of the Upper Permian Shanxi shale in southern Yan’an area, Ordos basin. A series of methods were comprehensively studied using high-pressure mercury intrusion, low-pressure N2 and CO2 adsorption and organic geochemical experiments, X-ray diffraction and scanning electron microscope observations to accurately analyze the material composition, pore feathers and its influencing factors of the transitional shale. The results indicate that the total organic carbon (TOC) content of the study shale varies of 0.12%~5.43%, with an average of 1.40%. The type of the organic matter (OM) belongs to type III and experiences in over maturity or dry gas window with an average Ro of 2.54%. An important characteristic of these shale is the large proportion of clay minerals content, which ranges from 40.70% to 87.00%, with an average of 60.05%, in which illite and kaolinite are the main components, accounting for 36.6% and 36.7% of the total clay minerals respectively, followed by chlorite and illite/smectite (I/S) mixed layer. The quartz content is between 10.6%~54.5%, with an average of 35.49%. OM pores are mostly circular bubble-shaped pores, and mostly micropores, while inorganic pores are well developed and mainly contributed by clay mineral pores and with mostly slit-type, plate-like, and of irregular polygon form. Mesopores are the major contributor to pore volume (PV), while micropores contribute the least to the PV. The contribution of micropores to the specific surface area (SSA) is greater than 61%, followed by mesopores. Macropores have almost no contribution to the development of the SSA. OM pores are the main contributor to the total specific surface area of the shale, with an average contribution rate of 61.05%, but clay mineral pores contribute more to the total pore volumes. In addition, both the content of chlorite and illite/smectite (I/S) mixed layer is positively correlated with the volume ratio of mesopores. It was found that high TOC, I/S mixed layer and chlorite content are all favorable conditions for the target shale in the study area.